Exploring the impact of growth mindset on psychological symptoms in students from ethnic regions of China: how meaning in life makes a difference - Fang, Zuozhi; Fu, Zhongfang (Frontiers in Psychiatry, 2025)
IntroductionDrawing on implicit belief theory, this study examines the relationship between growth mindset and psychological symptoms in adolescents from ethnic minority regions in China, with a focus on the mediating role of meaning in life. Understanding this mechanism can provide insights into protective factors that support adolescent mental health.MethodsStudy 1 employed a cross-sectional mediation model with 1,184 middle school students from Yunnan and Guangxi, using the Growth Mindset Scale, Meaning in Life Questionnaire, and Brief Symptom Inventory. Study 2 adopted a longitudinal mediation model, tracking 618 students over eight months. Multiple regression and structural equation modeling were used to assess direct and indirect effects, controlling for socioeconomic status and age.ResultsGrowth mindset was positively associated with meaning in life and negatively associated with psychological symptoms, including depression, anxiety, interpersonal sensitivity, and hostility. Longitudinal findings confirmed that growth mindset at T1 predicted lower psychological symptoms at T2, with meaning in life serving as a partial mediator. The mediation effects accounted for 21.55% to 43.33% of the total effect across different symptoms, indicating a cumulative impact over time.DiscussionThese findings highlight the protective role of growth mindset and the importance of meaning in life in adolescent mental health. The consistency of the mediation effect across cross-sectional and longitudinal models suggests that interventions promoting growth mindset and meaning-building strategies could have sustained mental health benefits. These insights have practical implications for school-based programs aimed at fostering resilience and psychological well-being in adolescents.